ARABIC-THE OPENING AND AFFIRMATION OF ITS ARAB IDENTITY IN LIGHT OF THE PROPHETIC SUNNAH - Ayman Jassim Mohammed Al-Doori (دی اسکالر)
This study aims to elucidate the Prophet's prophecy regarding the opening of Jerusalem, a part of the unseen knowledge bestowed by Allah upon His Prophet as a compelling proof of his prophethood. This study revolves around two main axes: firstly, the history of Jerusalem, demonstrating its Islamic Arab identity, and the corruption perpetrated by the Jews in the land, leading to their destruction by divine decree. Secondly, it examines the entry of Jerusalem into the protection of Islam and the establishment of its spiritual connection during the Prophet's Night Journey, alongside prophetic traditions heralding its opening and their interpretations, the subsequent conquests and reconciliations with its inhabitants under specific conditions, the Crusader occupation, its liberation by Salah al-Din al-Ayyubi, its subsequent fall to the Crusaders again, and the reasons behind it.